TRANSFORMATION OF INDONESIA'S MARITIME SOVEREIGNTY AFTER THE RECOGNITION OF THE UNITED NATIONS CONVENTION ON THE LAW OF THE SEA 1982 - Dina Aryanti (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the transformation of Indonesia's maritime sovereignty after the recognition of the United Nations Convention on the Law of the Sea 1982 (UNCLOS 1982) and its implications for national legal arrangements. Prior to the recognition of UNCLOS 1982, the regulation of Indonesia's maritime territory still referred to the Territoriale Zee en Maritieme Kringen Ordonantie 1939 which caused inter-island waters to be treated as high seas, thereby weakening national territorial integration. This study is a normative legal study employing statutory approach and conceptual approach. The results show that the recognition of the concept of an archipelagic state in UNCLOS 1982 provides legal legitimacy for Indonesia to establish archipelagic baselines, expand maritime jurisdiction, and affirm the sea as a unified national sovereign territory. UNCLOS 1982 also brought about a change in the conception of maritime sovereignty from its original absolute nature to differentiated sovereignty between full sovereignty in territorial seas and archipelagic waters with sovereign rights in the Exclusive Economic Zone and continental shelf. This transformation was then implemented through the harmonization of various national regulations concerning maritime affairs, waters, national territory, and Indonesia's EEZ. However, the implementation of Indonesia's maritime sovereignty still faces challenges in the form of overlapping maritime claims, the threat of violations at sea, and suboptimal maritime law enforcement.